Pemaknaan Pengalaman Culture Shock Mahasiswa Rantau pada Budaya di Lingkungan Kampus - Dian Nadila; Doddy Iskandar C (Bandung Conference Series: Public Relations, 2024)
Abstract. Culture shock is something that naturally happens to a migrant. Culture shock occurs when an individual enters a new environment with a different culture, so the habits, norms, customs and values that they have been familiar with cannot be applied in the new environment where they live. This phenomenon happened to overseas students from Bangka Belitung. In this case, they experience frustration with the situation, and find it difficult to initiate interactions in communicating with the community due to differences in vocabulary or dialect between Bangka Belitung and Bandung. This research aims to determine the meaning of the culture shock experience of overseas students and the adaptation process of overseas students from Bangka Belitung who experienced culture shock in the city of Bandung. This research uses a qualitative method with a phenomenological approach, the data sources used are primary and secondary data sources with the number of informants being 3 overseas students from Bangka Belitung. The results of this research are: Students from Bangka Belitung who migrated experienced culture shock directly without any outside interference. Adaptation to a new environment is an inevitable part of the learning experience outside the home area. The high cost of living in the city of Bandung is a major challenge, causing financial stress and language difficulties. The adaptation process through the euphoria phase, crisis phase, adjustment phase, and assimilation phase produces better emotional well-being with social support and individual abilities. Abstrak. Culture shock merupakan sesuatu yang alamiah terjadi pada seorang perantau. Culture shock terjadi ketika individu memasuki lingkungan baru dengan kebudayaan yang berbeda maka kebiasaan, norma, adat istiadat dan nilai yang selama ini dikenalnya tidak bisa diterapkan di lingkungan baru tempat tinggalnya tersebut. Penelitian ini bertujuan untuk mengetahui pemaknaan pengalaman culture shock mahasiswa rantau dan proses adaptasi mahasiswa rantau asal Bangka Belitung yang mengalami culture shock di Kota Bandung. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi, sumber data yang digunakan adalah sumber data primer dan sekunder dengan jumlah informan sebanyak 3 orang mahasiswa rantau asal Bangka Belitung. Hasil dari penelitian ini yakni: Mahasiswa asal Bangka Belitung yang merantau mengalami culture shock secara langsung tanpa ada campur tangan dari luar. Adaptasi terhadap lingkungan baru adalah bagian tak terhindarkan dari pengalaman belajar di luar daerah asal. Biaya hidup tinggi di Kota Bandung menjadi tantangan utama, menyebabkan tekanan finansial dan kesulitan berbahasa. Proses adaptasi melalui fase euforia, fase krisis, fase penyesuaian, dan fase asimilasi menghasilkan kesejahteraan emosional yang lebih baik dengan dukungan sosial dan kemampuan individu.